Decoding the Hayward kiwi (Actinidia deliciosa var Hayward) genome: transcriptomic responses to drought and salinity and AdhSAP4’s role in salinity stress responses - Parra, Samuel; Núñez-Lillo, Gerardo; Tapia-Reyes, Patricio; Carrasco-Lozano, Emerson Clovis; Porcile, Vincenzo; Gonzalez-Calquin, Christian; Amaza, Leticia; Quiroz, Luis Felipe; Meneses, Claudio; Handford, Michael; Norambuena, Lorena; Martínez, Juan Pablo; et al. (Frontiers in Plant Science, 2025)
Abiotic stresses such as drought and salinity pose major limitations to crop productivity, particularly in sensitive species like the Hayward kiwi (Actinidia deliciosa var. Hayward). Stress-associated proteins (SAPs), defined by conserved A20/AN1 zinc finger domains, are emerging as key modulators of plant stress responses. Despite their relevance in model plants, their functional roles in kiwi remain unexplored. In this study we assembled a high-quality haploid reference genome for Hayward kiwi, annotating 42,797 protein-coding genes. RNA-Seq profiling of in vitro leaves exposed to drought (20% PEG-6000) and salinity (200 mM NaCl) at 6 and 24 hours identified differentially expressed genes (DEGs). The differential gene expression kinetics between drought and salinity suggest distinct adaptation mechanisms. Fourteen SAP genes were identified, with AdhSAP4 showing salt-induced expression and homology to rice OsSAP7. Nuclear localization of AdhSAP4-GFP was confirmed, and transgenic tobacco lines overexpressing AdhSAP4 exhibited heightened salt sensitivity, reduced growth, and chlorophyll loss. This study establishes a genomic and transcriptomic framework for kiwi stress biology and confirms AdhSAP4 as a negative regulator of salinity tolerance. The evolutionary conservation of SAP function highlights their potential as biotechnological targets for enhancing stress resilience in perennial crops like kiwi.